2014
DOI: 10.1083/jcb.201401070
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy of damaged mitochondria occurs locally in distal neuronal axons and requires PINK1 and Parkin

Abstract: The Parkinson’s disease–associated proteins PINK1 and Parkin mediate local mitophagy of dysfunctional mitochondria in distal neuronal axons, abrogating the need for retrograde organelle transport and ensuring rapid neuroprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
418
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 441 publications
(436 citation statements)
references
References 64 publications
(127 reference statements)
17
418
1
Order By: Relevance
“…Robust basal mitophagy occurs in neurons (Maday et al, 2012), but it is unclear whether this constitutive process occurs through PINK1-and parkin-dependent or independent pathways (Allen et al, 2013;Bingol et al, 2014;Grenier et al, 2013;Strappazzon et al, 2014;Webster et al, 2013). By contrast, locally induced mitophagy in the axon has been shown to be dependent on both PINK1 and parkin (Ashrafi et al, 2014(Ashrafi et al, ). et al, 2012Jin et al, 2010;Meissner et al, 2011;Whitworth et al, 2008).…”
Section: Dynamics Of Mitochondrial Degradation In Neurodegenerative Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Robust basal mitophagy occurs in neurons (Maday et al, 2012), but it is unclear whether this constitutive process occurs through PINK1-and parkin-dependent or independent pathways (Allen et al, 2013;Bingol et al, 2014;Grenier et al, 2013;Strappazzon et al, 2014;Webster et al, 2013). By contrast, locally induced mitophagy in the axon has been shown to be dependent on both PINK1 and parkin (Ashrafi et al, 2014(Ashrafi et al, ). et al, 2012Jin et al, 2010;Meissner et al, 2011;Whitworth et al, 2008).…”
Section: Dynamics Of Mitochondrial Degradation In Neurodegenerative Dmentioning
confidence: 99%
“…However, localized damage to mitochondria in neuronal axons was also found to induce autophagosome formation locally (Ashrafi et al, 2014). As healthy mitochondria normally undergo bidirectional transport in axons, damaged mitochondria might be stalled in axons owing to release of the Milton/kinesin motor protein complex from mitochondria by PINK1 and parkin-dependent degradation of the adaptor Miro (Wang et al, 2011).…”
Section: Dynamics Of Mitochondrial Degradation In Neurodegenerative Dmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the effects of 298/9EE on mitochondrial dynamics when endogenous PINK1 was activated, we transfected rat hippocampal neurons with either with Myc-Miro or Myc-Miro298/9EE and applied 10 μM antimycin A to activate the PINK1/Parkin pathway (51). Antimycin A caused mitochondrial arrest in both populations (Fig.…”
Section: Mirot298et299e Inhibits Parkin Effects On Mitochondrial Dynmentioning
confidence: 99%
“…Mitochondrial dysfunction caused by overexpression of PINK1 or Parkin decreases the rate of mitochondrial transport in vitro and in vivo (36). Furthermore, a recent study using KillerRed demonstrated that local mitochondrial damage results in mitophagy in axons (37). Therefore, the acute loss of synaptic mitochondria in our model may result from defects in mitochondrial transport and/or mitophagy.…”
Section: Discussionmentioning
confidence: 90%